Therapeutic effectiveness of rat bone marrow stem cells in Poly Cystic Ovary Syndrome Mice Model on folliculogenesis, TGF-β, GDF-9 expression, and estrogen, TNF- and androgen Levels - Budi Santoso; Agus Sulistyono; Salmon Charles S; Widjiati Widjiati (Majalah Obstetri dan Ginekologi, 2016)
Objectives: to identify therapeutic effectiveness of Rat Bone Marrow stem cell in PCOS rats model on folliculogenesis, TGF-beta and GDF-9 expression and on estrogen, TNF-a and androgen levels.Material and Methods: this study is a laboratory experimental research with using animal testing. PCOS was induced by the administration of testosterone propionate hormone into 30 mice. The subjects of this study are divided into 2 groups: stem cell group and control group. The mice were injected with testosterone then vaginal swab was performed to determine the mice cycle. After determining mice in anestrous cycle, stem cell was injected. TNF-a was measured with immunohistochemistry and androgen was examined using ELISA. The data was measured by student t-test.Result: The average number of TNF-a expression in control group was lower than stem cell group (5.35 vs 2.34; p= 0.0026). The average androgen level for stem cell group was lower than mean for control group (2.31 vs 0.40; p= 0.0026).Conclusion: In this study of polycystic model mice, stem cell decreased the expression of TNF-a and androgen level